Front Cover: Solvent‐Enhanced Conformational Flexibility of Cyclic Tetrapeptides (ChemPhysChem 13/2019). Issue 13 (2nd July 2019) - Berger, Nadja; Wollny, Laura J. B.; Sokkar, Pandian; Mittal, Sumit; Mieres‐Perez, Joel; Stoll, Raphael; Sander, Wolfram; Sanchez‐Garcia, Elsa
Abstract : The Front Cover the structure of a cyclic tetrapeptide in solution. The dynamics of the peptide in explicit solvent was investigated using several computational and experimental techniques at different temperatures. More information can be found in the Article by N. Berger et al. onpage 1664 in Issue 13, 2019 (DOI:10.1002/cphc.201900345 ).